2020
DOI: 10.3390/ma13194437
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Rubberized Asphalt Using High-Content Rubber Powder

Abstract: Rubberized asphalt (RA) has been successfully applied in road engineering due to its excellent performance; however, the most widely used rubber content is about 20%.To improve the content of waste rubber and ensure its performance, seven rubberized asphalts with different powder content were prepared by high-speed shearing. Firstly, penetration, softening point, and ductility tests were carried out to investigate the conventional physical features of high-content rubberized asphalt (HCRA). Then, the dynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The scanning electron microscope (SEM) imaging revealed that the high concentrations of CR powder created an excellent network connection with virgin asphalt. The microscopy of asphalt with high rubber contents showed minor differences before and after ageing, and the compatibility and stability remained satisfactory even after extended ageing [26].…”
Section: Morphologymentioning
confidence: 91%
See 2 more Smart Citations
“…The scanning electron microscope (SEM) imaging revealed that the high concentrations of CR powder created an excellent network connection with virgin asphalt. The microscopy of asphalt with high rubber contents showed minor differences before and after ageing, and the compatibility and stability remained satisfactory even after extended ageing [26].…”
Section: Morphologymentioning
confidence: 91%
“…Tables 3-5 show that adding less than 20% CR enhanced the performance of CR-modified asphalts. In contrast, high rubberised asphalt contents of 20-50% imparted excellent high-temperature characteristics, low-temperature properties and fatigue resistance compared to virgin asphalt [26]. Figure 4 shows crumb rubber with varying particle sizes.…”
Section: Size and Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For rubberized asphalt, a rubber powder content of over 25% can become a high-content rubberized asphalt, and a large amount of research has proven the feasibility of high-content rubberized asphalt [11,12]. In recent years, it has been found that highcontent rubberized asphalt (HCRA) has better performance in terms of high-temperature rutting resistance and fracture resistance compared to ordinary RA [13,14]. Also, its asphalt mixtures have good rutting and fatigue resistance [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of CR and RAP binder modifications on the rheological characteristics were also investigated. Multiple studies showed that CR-modified binder (CRMB) has a lower phase angle (δ), higher shear modulus ( G *), higher rutting factor ( G */sin­(δ)), lower creep stiffness, and lower nonrecoverable strain after multiple stress–strain recovery cycles (MSCR) than virgin binders. Roja et al investigated the rheological characteristics of RAP binder mixed with a virgin binder (VRAPB), and they revealed that fatigue life and creep compliance significantly decrease while the rutting factor increases by elevating the RAP binder dosage . However, the binder behavior significantly changes by mixing the RAP binder with CRMB, where the binder performance does not show a consistent trend by changing the RAP binder or CR dosages.…”
Section: Introductionmentioning
confidence: 99%